Front Stage and Back Stage Sales Promotion Girls (SPG) in Car Dealer of PT Toyota Merdeka Motor (Toyota) Soreang Bandung Regency - Suminar, Ratna; Ratna Devi Sakuntalawati, Lv; Haryono, Bagus (KnE Social Sciences, 2024)
This study is an analysis of self-presentation, performance, and appearance of sales promotion girls (SPG) at Toyota Dealer in Soreang, Bandung Regency. The aim of this research is (1) to determine the front-stage presentation of SPG at PT Toyota Merdeka Motor in Soreang, Bandung Regency, and (2) to understand the backstage behavior of SPG at PT Toyota Merdeka Motor in Soreang, Bandung Regency. This research employs a qualitative descriptive method with a purposive sampling technique. Data collection techniques involve observation and document research. The primary informants for this study are the sales promotion girls of PT Toyota Merdeka Motor. The data analysis technique utilizes the interactive model by Milles and Huberman, involving data collection, data reduction, data presentation, and drawing conclusions. Data triangulation is also employed in the research analysis. The results of the study indicate that self-presentation is divided into front-stage and backstage behavior. The front-stage behavior includes the performance and appearance of sales promotion girls. There is a notable difference in the behavior of SPG at Toyota PT when they are on the front stage as opposed to when they are backstage. Keywords: dramaturgy, self-presenting, front stage, and backstage